2020
DOI: 10.3390/ijms21249413
|View full text |Cite
|
Sign up to set email alerts
|

The Central Region of Testican-2 Forms a Compact Core and Promotes Cell Migration

Abstract: Testicans are modular proteoglycans of the extracellular matrix of various tissues where they contribute to matrix integrity and exert cellular effects like neurite outgrowth and cell migration. Using testican-2 as a representative member of the family, we tackle the complete lack of general structural information and structure–function relationship. First, we show using isothermal titration calorimetry and modeling that extracellular calcium-binding domain (EC) has only one active calcium-binding site, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Midkine is a heparine-binding cytokine, which regulates processes like tissue protection and inflammation, additionally, it is present in senile plaques of AD and therefore is suggested as a potential clinical target ( 31 , 32 ). Testican-2 is a component of the extracellular matrix known for its calcium-binding properties ( 33 ) and it has been previously described to be accumulated in the brain of AD patients ( 34 , 35 ). Interestingly, all these proteins are known to be upregulated in AD patients and have been explored as AD biomarkers ( 35 , 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Midkine is a heparine-binding cytokine, which regulates processes like tissue protection and inflammation, additionally, it is present in senile plaques of AD and therefore is suggested as a potential clinical target ( 31 , 32 ). Testican-2 is a component of the extracellular matrix known for its calcium-binding properties ( 33 ) and it has been previously described to be accumulated in the brain of AD patients ( 34 , 35 ). Interestingly, all these proteins are known to be upregulated in AD patients and have been explored as AD biomarkers ( 35 , 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Testican-2 is a component of the extracellular matrix known for its calcium binding properties 33 and it has been previously described to be accumulated in the brain of AD patients 34,35 .…”
Section: 7-highly Overexpressed Protein Set Drives Neuroinflammationmentioning
confidence: 99%
“…SPOCK family comprised of SPOCK1, SPOCK2, and SPOCK3, and was originally identified by cDNA cloning, with amino acid homologies ( Vannahme et al, 1999 ; Bradshaw, 2012 ). SPOCK proteins share a unique N-terminal region, followed by a follistatin-like (FS) domain, calcium-binding (EC) domain, thyroglobulin type-1 (TY) domain, and a C-terminal tail encompassing heparan/chondroitin sulfate glycosaminoglycan attachment sites at two serine residues ( Alliel et al, 1993 ; Bonnet et al, 1996 ; Krajnc et al, 2020 ). To connect protein functions to the spatial organization of SPOCK2 protein domains, Krajnc et al (2020) confirmed that the FS-EC-TY domain triplet formed a structure core and was responsible for executing functions.…”
Section: Discussionmentioning
confidence: 99%
“…SPOCK family comprised of SPOCK1, SPOCK2, and SPOCK3, and was originally identi ed by cDNA cloning, with amino acid homologies (Bradshaw et al 2012;Vannahme et al 1999). SPOCK proteins share a unique N-terminal region, followed by a follistatin-like (FS) domain, calcium-binding (EC) domain, thyroglobulin type-1 (TY) domain, and a C-terminal tail encompassing heparan/chondroitin sulfate glycosaminoglycan attachment sites at two serine residues (Alliel et al 1993;Bonnet et al 1996;Krajnc et al 2020). To connect protein functions to the spatial organization of SPOCK2 protein domains, Krajnc et al con rmed that the FS-EC-TY domain triplet formed a structure core and was responsible for executing functions (Krajnc et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…SPOCK proteins share a unique N-terminal region, followed by a follistatin-like (FS) domain, calcium-binding (EC) domain, thyroglobulin type-1 (TY) domain, and a C-terminal tail encompassing heparan/chondroitin sulfate glycosaminoglycan attachment sites at two serine residues (Alliel et al 1993;Bonnet et al 1996;Krajnc et al 2020). To connect protein functions to the spatial organization of SPOCK2 protein domains, Krajnc et al con rmed that the FS-EC-TY domain triplet formed a structure core and was responsible for executing functions (Krajnc et al 2020). All three SPOCKs are extracellular proteoglycans highly expressed in brain, ovary, lung, testis, prostate, and kidney, and it is expected that SPOCKs might contribute to extracellular matrix and associate with tumor progression (Alliel et al 1993;Bonnet et al 1996;Vannahme et al 1999).…”
Section: Discussionmentioning
confidence: 99%